Pengaruh Model Quantum Learning (QL) Berbantuan Media Big Book Terhadap Kemampuan Membaca Teks Fabel Pada Siswa Kelas VII SMP PGRI Setu Bekasi - Rahmawati, Erina; Setiawan, Hendra; Muhtarom, Imam (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research aims to determine the effect of the Quantum Learning model assisted by Big Book media on the ability to read fable texts in class VII students at PGRI Setu Bekasi Middle School. The problem that arises in this school is students' lack of literacy interest in reading. Considering that at PGRI Setu Bekasi Middle School, teachers have not provided innovative and interesting learning models to stimulate students' reading skills. Quantitative approach to ensure data validity. The population in the research sample was class VII A as the control class and class VII B as the experimental class, each with a total of 36 students. The form of experimental research chosen by the researcher is a quasi-experimental design with a non-equivalent control group design. The research results were obtained using SPSS 25 For Windows. The average pretest score for the experimental class was 58, rising to 100 in the posttest, meaning that there was an influence from the application of the model because students' scores increased. Apart from that, the normality test of the data was normally distributed with pretest results for the control class 0.060>0.05 and posttest data for the control class 0.052>0.05. Experimental class pretest data 0.073> 0.05 and experimental class posttest data 0.200> 0.05. Then, the homogeneity test found that the control class value was 0.904 and the experimental class value was 0.915, which was declared homogeneous data. The N-gain test the experimental class was 0.56, which was interpreted as being in the medium category. Test the hypothesis using the Independent Sample test. Based on the specified criteria, if the sig. (2-tailed) is smaller than α 5% (sig. (2-tailed) < 0.05) or 0.000 < 0.050, meaning that Ho is rejected and Ha is accepted. Keywords: Reading ability, Quantum Learning, Big Book Media, Learning Model, Fable Text